Long-term post-marketing surveillance of mizoribine for the treatment of lupus nephritis: Safety and efficacy during a 3-year follow-up. (8th May 2014) - Yagi, Nobuyuki; Okada, Kenya; Sudo, Yohei; Itoh, Hiromichi; Yoshida, Hisao; Kuroda, Tatsuhiko
Objective: To determine the safety and efficacy of long-term use of mizoribine by undertaking a 3-year post-marketing surveillance study. Methods: Subjects were all lupus nephritis patients newly treated with mizoribine between 1 October 2003 and 30 September 2005 at contracted study sites. Results: Mizoribine was administered to 881 lupus nephritis patients in the safety analysis set consisting of 946 patients recruited from 281 contracted study sites after satisfying the eligibility criteria. There were 301 events of adverse drug reactions that were observed in 196 (20.7%) of the 946 subjects. There were 34 events of serious adverse drug reactions in 31 patients (3.2%). No deterioration in hematological and biochemical test values was observed, but immunological testing showed significant improvements in C3, CH50, and anti-DNA antibody titers. The negative rate of proteinuria also increased over time. The median steroid dosage was 15 mg/day at the commencement of treatment, but was reduced to 10 mg/day at 12 months and 8 mg/day at 36 months. Conclusion: The findings of the 3-year long-term drug use surveillance study indicated that mizoribine can be used over the long term with relatively few adverse drug reactions, suggesting its suitability for use in maintenance drug therapy.